PERILAKU AKTIVITAS PERDAGANGAN INTRAHARI DI BURSA EFEK JAKARTA - Luluk Kholisoh; Darmadi Darmadi (Jurnal Ilmiah Ekonomi Bisnis, 2011)
The primary objective of this study is to investigate the pattern of intraday tradingwithin industrial sector which are listed in LQ45 and the domination oftelecommuniaction sector in trading activities at the Jakarta Stock Exchange. Anexamination on the behavior of intraday stock trading activities at the Jakarta StockExchange in the period between 2002 and 2003 is accomplished in this study. Tradingactivities used in this study were volatility of return, volatility of stock price, volume oftrading (based on transactions), spread, relative spread, depth, and relative depth(based on order). Approximately 8 millions trading activities were particized into timeinterval of 30 minutes. Regression analysis with dummy variable for independentvariable was applied. Results of the study showed that there were high means oftrading activities both at the beginning and the end of trading. This finding is inaccordance with a number of theories and results of several empirical studies whichindicate that trading behaviors in each capital market are varied. In addition, it wasalso indicated that trading activities at the Jakarta Stock Exchange, rather than bytelecommunication sector, were dominated by financial sector.